2016
DOI: 10.1016/j.neuron.2016.04.031
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Regulation of Lateral Inhibition between Striatal Neurons Gates the Stimulant Actions of Cocaine

Abstract: SUMMARY Striatal medium spiny neurons (MSNs) form inhibitory synapses on neighboring striatal neurons through axon collaterals. The functional relevance of this lateral inhibition and its regulation by dopamine remains elusive. We show that synchronized stimulation of collateral transmission from multiple indirect-pathway MSNs (iMSNs) potently inhibits action potentials in direct-pathway MSNs (dMSNs) in the nucleus accumbens. Dopamine D2 receptors (D2Rs) suppress lateral inhibition from iMSNs to disinhibit dMS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
196
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(214 citation statements)
references
References 63 publications
16
196
2
Order By: Relevance
“…Interestingly, cocaine-induced locomotion is also diminished in iMSN-Drd2KO mice, but rescued by chemogenetic activation of G i signaling in iSPNs. Although it is not possible to exclude dendritic mechanisms with the approaches used, this work shows that cocaine-induced locomotion is gated by DA modulation of collateral transmission [72]. Consistent with this model, selective deletion of D2R from iSPNs alone increased GABAergic transmission presumably in part at collateral connections, decreased firing of both iSPNs and dSPNs, and caused hypokinesia [73].…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…Interestingly, cocaine-induced locomotion is also diminished in iMSN-Drd2KO mice, but rescued by chemogenetic activation of G i signaling in iSPNs. Although it is not possible to exclude dendritic mechanisms with the approaches used, this work shows that cocaine-induced locomotion is gated by DA modulation of collateral transmission [72]. Consistent with this model, selective deletion of D2R from iSPNs alone increased GABAergic transmission presumably in part at collateral connections, decreased firing of both iSPNs and dSPNs, and caused hypokinesia [73].…”
Section: Introductionmentioning
confidence: 67%
“…Moreover, it is almost impossible to selectively manipulate collateral synapses without affecting other connections in the striatum. The latter problem was recently circumvented by using a combination of novel genetic, optogenetic and chemogenetic techniques [72,73]. Dobbs et al found that lateral inhibition, evoked by optogenetically activating a cohort of iSPNs, strongly reduced intrinsic excitability of postsynaptic dSPNs in nucleus accumbens.…”
Section: Introductionmentioning
confidence: 99%
“…D2Rs are G i coupled receptors known to modulate neurotransmitter release at presynaptic terminals (Adrover et al, 2014; Dobbs, in press). We tested whether acute activation of G i signaling in iMSNs could revert the enhanced GABAergic transmission observed in iMSN-Drd2KO mice back to control levels.…”
Section: Resultsmentioning
confidence: 99%
“…Conceivably, dyskinesia induced by L-DOPA in PD could result from 2 main factors acting concomitantly, i.e., direct pathway "overactivation" via D1 receptors and indirect pathway "overinhibition" via D2 receptors. There are at least 2 mechanisms by which D2-mediated iSPN overinhibition may contribute to LID, (a) a failure to suppress competing movements when specific motor components are selected (2) and (b) a loss of the physiological lateral inhibition exerted by iSPNs onto dSPNs (49,50). A model whereby both dSPNs and iSPNs contribute to LID has important translational implications that will be discussed below.…”
Section: Discussionmentioning
confidence: 99%